Application Of Consumption Method With Eoq, Mmsl Forecasting And Abc-Ven Analysis In Pharmaceutical Briefing Management In Hospitals General Royal Prima Marelan - Afni Kartika, Ajeng; Girsang, Ermi; Wienaldi, Wienaldi; Novalinda Ginting, Chrismis (Publisher Cv. Inara, 2023)
Hospitals should plan for drug needs using accountable methods to avoid empty drugs. Good drug planning can improve pharmaceutical stock control in hospitals. The purpose of this study was to find out about the application of consumption methods with EOQ, MMSL and ABC-VEN forecasting in the management of pharmaceutical supplies in hospitals. This study used retrospective mix-method data, quantitative data and qualitative primary data. The research was conducted at RSU Royal Prima Marelan. The results showed that drug supply control using the EOQ method of getting drugs reordered: cefixime 200MG ordered at 447, ondacetron 4MG 740, gabapentin 300MG 706, ranitidine 25MG 1467, novorapid flexpen / 5